2013
DOI: 10.1309/ajcpwl36jxmresfh
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Reproducibility of Gynecologic Cytology Interpretation Using the FocalPoint System

Abstract: FocalPoint safely screened high-grade lesions, which can be valuable for high-workload routines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…Finally, LBC offers an opportunity to introduce a high level of internal quality assurance in cytological diagnoses with a reproducible use of computer-guided image screening [24] that potentially reduces the margin of false-negative results and enhances the sensitivity of the Pap test evaluation [25], besides permitting the implementation of combined analyses of cytology and HPV molecular tests [26]. It is important to mention that between 2009 and 2011 the National Institute of Science and Technology of the Diseases Associated to the Papillomavirus (INCT-HPV) performed an assessment study of molecular techniques and proposed new algorithms for cervical cancer screening, which showed a very high negative predictive value (>99%) and high sensitivity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, LBC offers an opportunity to introduce a high level of internal quality assurance in cytological diagnoses with a reproducible use of computer-guided image screening [24] that potentially reduces the margin of false-negative results and enhances the sensitivity of the Pap test evaluation [25], besides permitting the implementation of combined analyses of cytology and HPV molecular tests [26]. It is important to mention that between 2009 and 2011 the National Institute of Science and Technology of the Diseases Associated to the Papillomavirus (INCT-HPV) performed an assessment study of molecular techniques and proposed new algorithms for cervical cancer screening, which showed a very high negative predictive value (>99%) and high sensitivity [14].…”
Section: Discussionmentioning
confidence: 99%
“…El desempeño del Papanicolaou depende de una serie de factores 10 , entre los que se encuentra la calidad de toma de muestra; en este estudio, sólo 3,7% de las muestras fueron inadecuadas, indicando que, en Chile, la baja sensibilidad del Papanicolaou no estaría relacionada con este punto. Otro factor del desempeño es la interpretación del frotis.…”
Section: Discussionunclassified
“…Automation in the cytopathology lab may be helpful in reducing errors pertaining to smear preparation, staining, and mounting, yet cost may be an important limitation, especially in resource-limited settings. However, studies have concluded that the benefit of automation in quality out powers this limitation [13]. …”
Section: Discussionmentioning
confidence: 99%